STRATEGY OF SMEs IN FACING MARKET NEEDS IN THE COVID-19 PANDEMIC ERA: CULINARY SMEs IN MAKASSAR CITY - Lestari Musa, Dwi Anugerah; Tahir, Thamrin; Bado, Basri (RADJA PUBLIKA, 2023)
Research purposes; (1) Analyzing descriptively the strategies of SMEs in the culinary field using e-commerce, digital marketing, customer relationship marketing and market needs during the Covid 19 pandemic in Makassar City,(2) Testing and analyzing SME strategies in the culinary field, the influence of e-commerce on market needs during the Covid-19 pandemic in Makassar City, (3) Testing and analyzing UKM strategies in the culinary field, the influence of digital marketing on market needs during the Covid-19 pandemic in Makassar City , (4) Testing and analyzing the strategies of SMEs in the culinary field, the influence of customer relationship marketing on market needs during the Covid-19 pandemic in Makassar City. This research method is categorized as an explanatory survey, data collection technique using a questionnaire to 100 UKM players spread across four (3) types of businesses in the culinary sector, namely; restaurants, cafes and restaurants, the sampling technique was carried out in a simple random proportional manner according to the population spread over the types of SMEs in the culinary sector, in answering the research hypothesis analysis was usedstructural equation modelling (SEM). The research results show; based on descriptive analysis of respondents' perceptions in assessing research variables it can be proven that the SME strategy usese-commerce, digital marketing and customer relationship marketing to market needs during the Covid 19 pandemic, especially SMEs in the culinary sector in Makassar City. In addition, based on hypothesis testing it was found that (1) e-commerce has a positive and significant effect on market needs, (2) digital marketing has a positive and significant effect on market needs, and (3) customer relationship marketing has a positive and significant effect on market needs.